Facial biotype and maxillomandibular skeletal classification in Angolan patients with dentomaxillofacial anomalies - Yosvany Herrero Solano (Medisur)
Foundation: cephalometric measurements are a useful instrument in orthodontic care, since together with other cephalometric measurements they complete and guide the treatment plan that the specialist can draw up based on the resolution of dentomaxillofacial anomalies. Objective: to determine the comorbidity between facial biotype and maxillomandibular skeletal classification in Angolan patients with dentomaxillofacial anomalies. Methods: a cross-sectional descriptive study was carried out at the Meditex Clinic, in Luanda, Angola, from August/2021 to July/2023. The studied population was 123 patients’ profile teleradiographs with dentomaxillofacial anomalies, admitted to the Orthodontic clinic. For the analysis of the profile teleradiography, measurements of the Ricketts and Steiner cephalogram were made, and the Facad software version 3403 was used. The maxillomandibular skeletal classification (class I, class II, class III) and the facial biotype (dolichofacial, mesofacial, brachyfacial) were studied. Results: 46.34% of patients presented maxillomandibular skeletal class II. Using the Ricketts VERT index, 49.59% of cases were classified as dolichofacial, followed by 42.27% as brachyfacial. 83.60% of patients with dolichofacial biotype were characterized by having maxillomandibular skeletal class II, and 76.92% of those with brachyfacial biotype were classified as class III. A significant association was found between facial biotype and maxillomandibular skeletal classification (p= 0.000). Conclusions: in the majority of patients with dentomaxillofacial anomalies, a relationship was evident between the dolichofacial biotype and the maxillomandibular skeletal class II, so there is a comorbidity between both skeletal-facial characteristics.